1981
DOI: 10.1128/jb.146.3.914-919.1981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of a mutation conferring sensitivity to bacteriophage Mu in Salmonella typhimurium LT2

Abstract: Two strains of Salmonella typhimurum LT2, SA1475 and MA411, were fortuitously found to be sensitive to bacteriophage Mu. The Mu-sensitivity allele of SA1475 was called musAl and shown to be linked to the histidine operon both in conjugation and transduction experiments. The Mu8 allele of MA411 was unlinked to the his region and was tentatively designated musB2. Strains carrying large deletions of the his operon were also tested for Mu sensitivity; those in which the his-rfb region is deleted were also sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…None of the MNNG-induced transductants exhibited increased transduction by the heterogenotic DNA. (Mergeay et al, 1981). This antimutator phenotype was previously reported in E. coli by Geiger & Speyer (1977).…”
Section: Mnng-induced Trp+ Recombinants Tested For Increased Transdsupporting
confidence: 79%
See 1 more Smart Citation
“…None of the MNNG-induced transductants exhibited increased transduction by the heterogenotic DNA. (Mergeay et al, 1981). This antimutator phenotype was previously reported in E. coli by Geiger & Speyer (1977).…”
Section: Mnng-induced Trp+ Recombinants Tested For Increased Transdsupporting
confidence: 79%
“…It is possible that, in order to survive MNNG treatment and give rise to a recombinant, cells must mutate as they do. Perhaps these mutations (like those exhibiting the 'antimutator' phenotype: Mergeay et al, 1981) or others found during the experiments shown in Fig. 3 are more frequent in MNNG survivors.…”
Section: Discussionmentioning
confidence: 73%
“…Another has been to select mutants of Salmonella spp. that are sensitive to Mu infection (117). A fourth method has been to use Mu dl with a helper Mu phage which has tail fiber genes derived from Pl.…”
Section: Construction Of Operon Fusionsmentioning
confidence: 99%
“…Bacterial strains were derivatives of S. Typhimurium strain LT2. LT2 is resistant to Mu infection, but a single mutation, musA, confers sensitivity (Faelen et al, 1981). Strain NH742 is an LT2 musA MupAp1 lysogen.…”
Section: Bacterial Strains Phage and Mediamentioning
confidence: 99%